Eligibility‐Identification Difficulty and Self‐Reported Preventive Care Implementation Among Japanese Primary Care Physicians - Hironori Yamada; Kei Miyazaki; Makito Yaegashi; Kuniko Nakayama; Rei Suganaga; Nobuaki Kusaka; Wataru Hirohashi; Tomio Suzuki (Journal of General and Family Medicine, 2026)
ABSTRACT Background Primary care is an important setting for prevention, but implementation gaps may arise before clinicians can identify patients eligible for preventive services. We described self‐reported preventive care implementation among Japanese primary care physicians and examined whether lower implementation co‐occurred with eligibility‐identification difficulty. Methods We conducted a nationwide web‐based cross‐sectional survey of physician members of the Japan Primary Care Association from May to June 2025. Respondents reported recommendation consistency for 30 preventive services, difficulty identifying eligible patients, and perceived barriers. Service‐level implementation and eligibility‐identification difficulty were summarized in a two‐axis map. Results Among 258 respondents, 56.2% reported structured preventive care training and 53.9% used outpatient reminders. “Mostly achieved” recommendation was relatively high for hypertension, diabetes, and dyslipidaemia screening and influenza vaccination, but low for screening for domestic violence, chlamydia/gonorrhea, abdominal aortic aneurysm, anxiety, and depression, respiratory syncytial virus vaccination, and folic acid counseling. Difficulty identifying eligible patients was highest for domestic violence screening (14.0%), chlamydia/gonorrhea screening (13.6%), hepatitis C screening (10.5%), and respiratory syncytial virus vaccination (7.8%). Common barriers were time constraints, insufficient knowledge or skills, low patient interest, and financial or reimbursement issues. Conclusions Self‐reported implementation varied substantially across services. Some low‐implementation services also involved eligibility‐identification difficulty, suggesting an upstream implementation problem. Japanese primary care may need systems that make eligibility visible through training, reminders, prompts, registries, and team‐based workflows.